Social-ecological systems in the Anthropocene: The need for integrating social and biophysical records at regional scales. (December 2015) - Dearing, JA; Acma, B; Bub, S; Chambers, FM; Chen, X; Cooper, J; Crook, D; Dong, XH; Dotterweich, M; Edwards, ME; Foster, TH; Gaillard, M-J; et al.
Understanding social-ecological system dynamics is a major research priority for sustainable management of landscapes, ecosystems and resources. But the lack of multi-decadal records represents an important gap in information that hinders the development of the research agenda. Without improved information on the long-term and complex interactions between causal factors and responses, it will be difficult to answer key questions about trends, rates of change, tipping points, safe operating spaces and pre-impact conditions. Where available long-term monitored records are too short or lacking, palaeoenvironmental sciences may provide continuous multi-decadal records for an array of ecosystem states, processes and services. Combining these records with conventional sources of historical information from instrumental monitoring records, official statistics and enumerations, remote sensing, archival documents, cartography and archaeology produces an evolutionary framework for reconstructing integrated regional histories. We demonstrate the integrated approach with published case studies from Australia, China, Europe and North America.